Improving Student Learning Outcomes Through Project Based Learning Model Assisted by Proteus 8 Professional Application at SMKN 2 Payakumbuh - Wahyu, Rifkhan; Thamrin, Thamrin (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2025)
This research aims to enhance students' learning outcomes in the subject of Electronic Circuit Applications by implementing the Project-Based Learning (PjBL) model, supported by the use of the Proteus 8 Professional application at SMK Negeri 2 Payakumbuh. The study is motivated by the low level of student engagement, lack of learning motivation, and the continued use of conventional teaching methods that fail to connect the subject matter with real-world contexts. This research employs a quantitative approach with a one-group pretest-posttest design. The participants of the study were eleventh-grade students enrolled in the Industrial Electronics Engineering program. Data were collected through tests administered before and after the implementation of the learning model. The analysis revealed a significant improvement in student performance following the use of the PjBL model integrated with Proteus 8 Professional. These results suggest that combining project-based learning with digital simulation tools fosters a more engaging, relevant, and effective learning experience, particularly in strengthening students’ conceptual understanding and practical abilities in electronics.